2023
DOI: 10.1039/d3dt01443f
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-driven organic oxidation over CdS-doped metal–organic frameworks

Abstract: In this research, we synthesized CdS nanoparticles doped metal-organic frameworks CdS@DUT-52 with different contents, using solvothermal method. CdS@DUT-52 possess strong light-absorption ability and effective electron-hole separation property, which proved by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…It has been reported that catalysts can activate molecular O 2 to generate reactive oxygen species such as 1 O 2 through energy transfer and O 2 ˙ − through electron transfer. 17,58–60 Here, formation of O 2 ˙ − was further confirmed by EPR experiments with 5,5-dimethyl-1-pryyoline- N -oxide (DMPO) as the trapping reagent of O 2 ˙ − . As shown in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…It has been reported that catalysts can activate molecular O 2 to generate reactive oxygen species such as 1 O 2 through energy transfer and O 2 ˙ − through electron transfer. 17,58–60 Here, formation of O 2 ˙ − was further confirmed by EPR experiments with 5,5-dimethyl-1-pryyoline- N -oxide (DMPO) as the trapping reagent of O 2 ˙ − . As shown in Fig.…”
Section: Resultsmentioning
confidence: 81%